Stages, Essence and Methodology of Experimental Work on Future Borderguard Officers’ Communicative and Discursive Culture Formation - Olha Babich; Ihor Bloshchynskyi (Pedagogical Discourse, 2017)
In the article the stages, essence and methodology of experimental work on future borderguard officers’ communicative and discursive culture (CDC) formation during their professional training has been grounded. During the experiment thorough studying of individual and social and psychological peculiarities of cadets was held, the communicative behavior in special service situation was analyzed. Research and experimental work was organized in three stages of scientific and pedagogical research. During the first stage the analysis of pedagogical, psychological and philosophic literature was held on the issues of CDC formation of future border guard officers, the discrepancies were defined, the scientific grounds were formulated, and experimental basis of the research was defined. During the second stage the initial experiment was held, structural and functional model of CDC of future border guard culture was made, experimental check of suggested conditions was conducted, the control over the dynamics of CDC formation of cadets was conducted, the necessary corrections were made with the purpose of improving the levels of this phenomenon formation. During the third stage the basic regulations of research were corrected, the materials were generalized and systematized, experimental programs of disciplines and electronic educational and methodical complexes for disciplines of general and professional training blocks were made and implemented, basic conclusions and recommendations as for the implementation of pedagogical experiment results in the process of professional training of future border guard officers were formulated. The presented results of the formational experiment indicate that statistically important changes happened in structural components and levels of communicative and discursive culture formation of cadets from experimental groups. Experimental data show that slight natural progress of levels of CDC formation of cadets happen too but those changed didn’t reach the level of statistic importance and reflect probably general improvement of CDC of future border guard officers. That’s why formational experiment in general proved the validity of stated hypothesis as for the effectiveness of pedagogical conditions for the formation of CDC of future border guard officers.Key words: future border guards officers, pedagogical experiment, communicative and discursive culture.